The Molecular Mechanism of Yellow Mushroom (Floccularia luteovirens) Response to Strong Ultraviolet Radiation on the Qinghai-Tibet Plateau - Guo, Jing; Xie, Zhanling; Jiang, Hongchen; Xu, Hongyan; Liu, Baolong; Meng, Qing; Peng, Qingqing; Tang, Yongpeng; Duan, Yingzhu (Frontiers in Microbiology, 2022)
The Qinghai-Tibet Plateau (QTP) is the highest plateau in the world, and its ultraviolet (UV) radiation is much greater than that of other regions in the world. Yellow mushroom (Floccularia luteovirens) is a unique and widely distributed edible fungus on the QTP. However, the molecular mechanism of F. luteovirens’s response to strong UV radiation remains unclear. In this study, we assembled the RNA sequence of UV-affected F. luteovirens at different stages. The results showed that in response to strong UV radiation, a total of 11871 significantly different genes were identified, of which 4444 genes in the vegetative mycelium (VM) stage were significantly different from the young fruiting bodies (YFB) stage, and only 2431 genes in the YFB stage were significantly different from fruiting bodies (FB) stage. A total of 225 differentially expressed genes (DEGs) were found to be involved in environmental signal transduction, biochemical reaction preparation and stress response pathway, pigment metabolism pathway, and growth cycle regulation, so as to sense UV radiation, promote repair damage, regulate intracellular homeostasis and reduce oxidative damage of UV radiation. On the basis of these results, a molecular regulation model was proposed for the response of F. luteovirens to strong UV radiation. These results revealed the molecular mechanism of adaptation of F. luteovirens adapting to strong UV radiation, and provided novel insights into mechanisms of fungi adapting to extreme environmental conditions on the QTP; the production the riboflavin pigment of the endemic fungi (Yellow mushroom) in the QTP was one of the response to extreme environment of the strong UV radiation.